1999
DOI: 10.1093/ps/78.12.1695
|View full text |Cite
|
Sign up to set email alerts
|

Trace elements in soils fertilized with poultry litter

Abstract: Poultry litter is used on agricultural land because of its high nutrient content. The litter contains trace elements. With land application of litter, these elements may accumulate in the soil or plants, may be transported as run-off to surface water, or may be leached into groundwater. The objective of this research was to measure the concentrations of trace elements in soils fertilized with poultry litter. Soil was collected from three agricultural farms in Wicomico County, MD. These farms had a long history… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
64
2
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(73 citation statements)
references
References 13 publications
5
64
2
2
Order By: Relevance
“…The enrichment of regulated metals at both sites was consistent with previous findings that showed the accumulation of Cd, Cr, Cu, Ni, Pb, and Zn in the 0-15 cm depth of soil following sludge application to a different type of soil (Chang et al, 1984). A similar accumulation of Cd, and Cu was found in soils fertilized with poultry litter (Gupta and Charles, 1999). Au and Ag are retained in soils under long-term application of biosolids (McBride et al, 1997).…”
Section: Metal Profiles At Different Soil Depthssupporting
confidence: 90%
“…The enrichment of regulated metals at both sites was consistent with previous findings that showed the accumulation of Cd, Cr, Cu, Ni, Pb, and Zn in the 0-15 cm depth of soil following sludge application to a different type of soil (Chang et al, 1984). A similar accumulation of Cd, and Cu was found in soils fertilized with poultry litter (Gupta and Charles, 1999). Au and Ag are retained in soils under long-term application of biosolids (McBride et al, 1997).…”
Section: Metal Profiles At Different Soil Depthssupporting
confidence: 90%
“…Much of this concern centers on litter's contribution of nutrients to runoff. However, there is growing concern over the potential for land-applied litter to contribute other contaminants to runoff water (Kingery et al 1994;Moore 1998;Gupta and Charles 1999;Church et al 2010).…”
mentioning
confidence: 99%
“…Gupta and Charles (1999) examined litter from research and commercial houses and reported significant variability in trace element content in association with differences in management practices. On average, litter tested in that study contained 37 mg As kg ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The problem appears when the poultry litters are contaminated by chemical elements. These elements may accumulate in the soils or plants or may be leached into groundwater [25].…”
Section: Discussionmentioning
confidence: 99%